Technologies of preparation of elementary school teachers for inclusive education in the process of continuous professional development. - Rizayeva Shalola Mamir qizi (Genius Publishing Group, 2023)
Professional-methodical training of teachers is reflected in the main areas of professional activity, such as knowledge of professional activity, organization of educational process, self-development. This, in turn, requires the teacher to have a perfect knowledge of the teaching of his subject and to apply it, to acquire the basic competencies necessary for designing, organizing and evaluating the educational process, as well as teaching and the educational process requires intensive organization based on innovative scientific achievements in the field of education, modern pedagogical and information and communication technologies, continuous and systematic self-development. Information about technologies is given.
Keywords: Continuing education; elementary school; inclusive education